10.6k views
2 votes
Solve: 2 ln 3 = ln(x - 4) x = 9 x = 10 x = 13

User Jhujhul
by
5.0k points

2 Answers

2 votes

Answer:

C on Edge x = 13 x =

-4 and x = 4

the solution is x = 4

Explanation:

I just did the assignment on edge.

User Superstar
by
5.0k points
4 votes

Solve: 2 ln 3 = ln(x - 4)

a)x = 9

b)x = 10

c)x = 13

Answer:

x = 13

Explanation:

To solve the problem above, we will follow the steps below;

2 ln 3 = ln(x - 4)

[using logarithm rule aInb = Inbᵃ]

so also our equation becomes

In 3² = In (x-4)

The In at the left-hand side of the equation will cancel-out the In at the right-hand side of the equation

Our equation becomes;

3² = x- 4

9 = x-4

add 4 to both-side of the equation in other to make x subject of the equation

9 + 4 = x-4 + 4

13 = x

x = 13

User Vladr
by
5.8k points